Plastic karma. Raccolta, riuso, riciclo e consacrazione buddhista dei rifiuti urbani in Thailandia - Rossi, Amalia (Antropologia Pubblica, 2025)
This paper outlines a first interpretative hypothesis around an increasingly articulated repertoire of ecological practices that have arisen in the Buddhist milieu in urban contexts of Southeast Asia, particularly in Thailand. The production of monastic robes from recycled plastic collected in the canals of Bangkok and in provincial cities is an example of how the decades-long commitment of eco-Buddhist environmentalism, which arose in Thailand in rural areas around the problem of deforestation, has been extending since 2010 to urban areas, and to the waste recycling sector. The aim is then to describe the new forms of social and cultural life that accompany these practical and ideological transformations of Buddhist religiosity in urban contexts and that lead activist monks to build new networks and to rethink the critical spaces, both terrestrial and aquatic, of Thai cities. The case of the Chak Daeng temple, located in the southern skirts of the mega city of Bangkok, will be scrutinized, as it shows the capability of engaged Buddhist monks and lay people to interact with associative networks, also meeting the interests of local institutions and those of the corporate and the business sectors, in the realization of socio-environmental projects where ecological “transition” and “conversion” can sometimes coincide. This case-study also shows that the appeal of religious authorities to the “sustainability” of lifestyles and urban production/consumption practices may pass through ecosophical speculations on the “sacred” nature of the material world.